KAJIAN GEOLOGI UNTUK MENENTUKAN AIR TANAH DAERAH SAMBIREJO, KECAMATAN PRAMBANAN, KABUPATEN SLEMAN, YOGYAKARTA - Trianda, Obrin; Nur'aini, Siti (Institut Teknologi Nasional Yogyakarta, 2021)
Sambirejo area (Prambanan Sub-District, Sleman District) is known as a water-scarcity area. The morphology shows as a hilly slope with is arranged by three lithology unit such as Semilir Formation (tuff sandstone and pumice breccia), Nglanggeran Formation (pyroclastic breccia) and alluvial unit. By having increasing number of population will be followed by fresh water needs of citizen, it will cause water-scarcity problems. Three aspects that controlling the fresh water availability in one area are morphology, lithology type and the depth of water table.The objective of this study is to investigate fresh-water resources in Sambirejo area. The problem arises is how to identify the good quality of water resource and also could be beneficial to fulfill the citizen’s water needs. Subsurface water management is still need to be conducted to gain the maximum water resources and soon after could be used directly by the citizen. The method of study firstly is geological mapping with the purpose of to identify the lithology distribution. Then the second is geo-electric resistivity to determine the fresh-water resources.Sambirejo area is known as a scare-water area due to the lithology composition such as breccia and tuff which is situated to the slope and ridge morphology. Water table presents at the depth between 20 to 40 meter is known as shallow aquifer whereas at the depth of 98 to 142 meter is categorized as almost deep aquifer. The typical of Sambirejo’s aquifer develops as a leaky unconfined aquifer where the lowest part of pumice breccia lithology is located impermeable tuff rock. Keywords: aquifer, lithology, fresh-water, Sambirejo